1990
DOI: 10.1161/01.str.21.11.1594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-arterial tissue plasminogen activator and urokinase on autologous arterial emboli in the cerebral circulation of rabbits [corrected].

Abstract: We conducted a randomized, blinded controlled trial to test the efficacy of fibrinolytic therapy with tissue plasminogen activator and urokinase in the treatment of acute embolic stroke. Embolic stroke was simulated in rabbits by injecting three 0.5x0.5 mm fragments of autologous arterial thrombus harvested from a traumatized auricular artery. Thirty minutes after embolization the rabbits were blindly treated with tissue plasminogen activator (n=21), urokinase («=20), or 0.9% saline (n=20). At 6 hours the rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 26 publications
(6 reference statements)
3
16
1
2
Order By: Relevance
“…The absence of hemorrhagic change in the ischemic areas of the brains of our rabbits accords with the findings of Benes et al 6 (using rabbits treated with a 1 mg t-PA bolus 30 minutes after embolization, then 1 mg/kg/hr infusion for 2 hours and killed 6 hours later) and of Chehrazi et al 22 (dosage as above and killed immediately after completion of treatment), as well of Slivka and Pulsinelli 29 (whose animals survived 30 hours after receiving a single bolus of streptokinase 1 hour postembolization). These latter authors also found that hemorrhagic transformation of the stroke was common when treatment was delayed for 24 hours with 7-9 hours' subsequent survival.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The absence of hemorrhagic change in the ischemic areas of the brains of our rabbits accords with the findings of Benes et al 6 (using rabbits treated with a 1 mg t-PA bolus 30 minutes after embolization, then 1 mg/kg/hr infusion for 2 hours and killed 6 hours later) and of Chehrazi et al 22 (dosage as above and killed immediately after completion of treatment), as well of Slivka and Pulsinelli 29 (whose animals survived 30 hours after receiving a single bolus of streptokinase 1 hour postembolization). These latter authors also found that hemorrhagic transformation of the stroke was common when treatment was delayed for 24 hours with 7-9 hours' subsequent survival.…”
Section: Discussionsupporting
confidence: 93%
“…27 Thus, although the use of arterial thrombus in our model somewhat complicated the experimental procedure, we, like others, 6 ' 23 considered this to be acceptable because the resulting emboli more closely resembled those found in humans than if we had employed emboli prepared from clotted venous blood. However, whereas Benes et al 6 injected t-PA directly into the previously embolized ICA, which presumably produced a very high concentration of t-PA at the site of embolism, we gave t-PA by the intravenous route, on the basis that the highly sophisticated interventional neuroradiological techniques for thrombolysis, such as those described by Zeumer et al, 24 are unlikely to be available for most stroke victims in the immediate future.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…After we began following the internal carotid artery to the skull base and occluding the occipital artery when it rose from the internal carotid, the incidence of ischemic injury in control animals increased to 85%. 2 We prefer to use temporary vessel clips to exclude the occipital artery from the experimental field. When this is accomplished, the embolic material will be consistently directed into the cerebral circulation, thereby minimizing experimental variability.…”
Section: Discussionmentioning
confidence: 99%